Health Education and Family Empowerment in Preventing Nutritional Problems in Early Childhood - Siregar, Fazidah Aguslina (Talenta Publisher Universitas Sumatera Utara, 2023)
Early childhood producing future human resources, is a group that is susceptible to a variety of health issues and nutritional disorders. It is important to pay attention to the fulfillment of excellent nutrition and to optimize every stage of its growth. According to estimates, 10% of the children in the Amanah Kahmi playgroup are malnourished due to nutritional abnormalities, and many parents lack awareness of the importance of feeding children a healthy diet. It could impact the risk of infectious disease and growth issues. This activity aims to inform parents about the monitoring of a child's nutritional condition and the preparation of nourishing foods for young children. The activity began with education on assessing children's nutritional status and putting it into practice by measuring the height and weight of 35 school students and then applying it using the WHO child nutrition monitoring chart. The results showed that 19 children with normal weight categories consisting of 5 boys and 14 girls; 8 children with poor nutritional status consisting of 7 boys and 1 girl; and 8 children close to the normal nutritional limit, consisting of 2 girls and 6 boys. The activity was followed by educating parents regarding balanced nutrition for children through the video presentation and preparation of nutritious food for children. This activity is expected to increase knowledge and assist parents in monitoring the growth and development of children and providing nutritious food for children to prevent nutritional disorders in early childhood.